2014
DOI: 10.1177/1740774514537136
|View full text |Cite
|
Sign up to set email alerts
|

Are missing data adequately handled in cluster randomised trials? A systematic review and guidelines

Abstract: Missing data are present in the majority of cluster randomised trials. However, they are poorly reported, and most authors give little consideration to the assumptions under which their analysis will be valid. The majority of the methods currently used are valid under very strong assumptions about the missing data, whose plausibility is rarely discussed in the corresponding reports. This may have important consequences for the validity of inferences in some trials. Methods which result in valid inferences unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 41 publications
1
68
0
Order By: Relevance
“…This review used a set of CRTs previously identified using a published electronic search strategy [27]. CRTs were eligible for inclusion if they were published in English in 2011.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This review used a set of CRTs previously identified using a published electronic search strategy [27]. CRTs were eligible for inclusion if they were published in English in 2011.…”
Section: Methodsmentioning
confidence: 99%
“…They were excluded if they were quasi-experimental; were pilot, feasibility, or preliminary studies; did not collect any data at the individual level; only assessed cost-effectiveness; or were not the primary report of the trial findings. Trials were identified from PubMed using a pre-specified search strategy [27]. We randomly selected 100 of the 132 eligible trials for inclusion in this current review using randomly generated numbers in the statistical software package Stata.…”
Section: Methodsmentioning
confidence: 99%
“…Two recent reviews 6,96 indicate that missing outcome data is common in GRTs, though investigators frequently analyze only available data without accounting for the missing data pattern. When the covariate-dependent missingness (CDM) assumption is plausible, both mixed effects and GEE models provide unbiased estimates of the intervention effect when the CDM covariates are included in an analysis of all available data.…”
Section: Developments To Address Data Challengesmentioning
confidence: 99%
“…There are various approaches to imputation of missing posttest data to choose from (Díaz-Ordaz et al, 2014), depending on whether differential provider effects are taken into account (Taljaard, Donner, & Klar, 2008) plete pretest-to-posttest data). Consequently, the single-level regression-based approach diminishes differences between providers, whereas the multilevel approach takes these differences into account.…”
Section: Strengthsmentioning
confidence: 99%